2022
DOI: 10.1002/jbt.23172
|View full text |Cite
|
Sign up to set email alerts
|

The pyrethroid insecticide permethrin confers hepatotoxicity through DNA damage and mitochondria‐associated apoptosis induction in rat: Palliative benefits of Fumaria officinalis

Abstract: Permethrin (PER) is a pyrethroid pesticide that is extensively used as an insecticide in world because of its high activity and its low mammalian toxicity. The current study was conducted to investigate the protective action of Fumaria officinalis against PER‐induced liver injury in male rats. However, HPLC‐DAD showed the richness of 6 components in F. officinalis (F) including quercetin, ferulic acid, and naringenin which were the most abundant. Total polyphenols, total flavonoids, and condensed tannins were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The improvements were visible under liver histopathology analysis, which saw a significant recovery from the PER-induced vacuolation and fragmentation of chromatin. F. officinalis also significantly decreased the DNA damage induced by PER, which could be due to quercetin, which is known to protect liver cells against mercury-induced DNA injury and redox status alterations [14] . The ethanolic extract at a dose of 200 and 500 mg/Kg body weight, showed significant (p<0.001) action against carbon tetrachloride induced liver damage, by reducing the serum marker enzymes like SGPT, SGOT and ALP.…”
Section: Hepatoprotectivementioning
confidence: 88%
See 3 more Smart Citations
“…The improvements were visible under liver histopathology analysis, which saw a significant recovery from the PER-induced vacuolation and fragmentation of chromatin. F. officinalis also significantly decreased the DNA damage induced by PER, which could be due to quercetin, which is known to protect liver cells against mercury-induced DNA injury and redox status alterations [14] . The ethanolic extract at a dose of 200 and 500 mg/Kg body weight, showed significant (p<0.001) action against carbon tetrachloride induced liver damage, by reducing the serum marker enzymes like SGPT, SGOT and ALP.…”
Section: Hepatoprotectivementioning
confidence: 88%
“…Scavenging activity of the extract on radicals with: IC 50 of 0.02 mg/g on DPPH, 0.01 mg/g on FRAP, and 0.14 mg/g on H2O2, which compares with IC 50 values of vitamin C of 0.014, 0.01 and 0.02 respectively. The total antioxidant capacity of F. officinalis extract was 258.79 mg GAE/g dry weight [14] .While some studies have found a correlation between the total amount of phenolics and the antioxidant activity, other studies have not found such correlation. This may be due to the presence of other antioxidant phytochemicals and synergistic effects among them, and to the fact that not all phenolic compounds have the same antioxidant activity.…”
Section: Antioxidant Activitymentioning
confidence: 89%
See 2 more Smart Citations